2018
DOI: 10.14196/mjiri.32.37
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the earnings of specialist physicians and nurses before and after implementing the Iran’s New Tariffs Book

Abstract: Background: The fair wage to specialist physicians and nurses can enhance their job motivation, quality of work, job satisfaction level, and improve the delivery of services to patients. The present study aimed to compare the proportion of changes in earnings of specialist physicians and nurses before and after implementing the Iran’s New Tariffs Book and compare their average income with a number of selected countries. Methods: This descriptive-analytical study was conducted cross-sectional in the hospitals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Proper salaries are one of the main strategies to attract and retain the workforce [ 50 ]. Payments in the Iranian health system to non-medical workforces are based on the combination of fixed salaries and performance-based payments, and nurses cannot obtain additional incomes through the provision of private services in government-run healthcare settings [ 51 ].…”
Section: Nursing Profession In Iranmentioning
confidence: 99%
See 2 more Smart Citations
“…Proper salaries are one of the main strategies to attract and retain the workforce [ 50 ]. Payments in the Iranian health system to non-medical workforces are based on the combination of fixed salaries and performance-based payments, and nurses cannot obtain additional incomes through the provision of private services in government-run healthcare settings [ 51 ].…”
Section: Nursing Profession In Iranmentioning
confidence: 99%
“…Payments in the Iranian health system to non-medical workforces are based on the combination of fixed salaries and performance-based payments, and nurses cannot obtain additional incomes through the provision of private services in government-run healthcare settings [ 51 ]. Studies in Iran have shown that the bulk of the healthcare sector’s expenditures in all healthcare settings is mainly dedicated to physicians [ 50 ]. However, health care depends on teamwork and team members need to receive a fair income.…”
Section: Nursing Profession In Iranmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the pressure of sanctions has been placed on the Iranian government and has caused many economic challenges that, in turn, influence the economic status of the healthcare delivery systems (Moradi-Lakeh and Vosoogh-Moghaddam, 2015;Setayesh and Mackey, 2016). Furthermore, lack of justice in the healthcare system and inequality in the benefits received by physicians and nurses decrease their QWL, job satisfaction level and quality of the delivery of services to the patients (Mazdaki et al, 2018).…”
Section: Research Background and Hypotheses Developmentmentioning
confidence: 99%
“…We believe that the reason for this is the atmosphere in Iran hospitals where there is a superiority of medical practitioners. In fact, medical practitioner has a dominance in Iran healthcare system in terms of income and authority compared to other professions [17]. This monopoly, may cause many staff, especially nurses, to feel incompetent and it might affect the quality of their performance.…”
Section: Discussionmentioning
confidence: 99%